Association between obstructive sleep apnea and sleep quality - Egon Ilman Saputra; Bambang Suprayogi Resi Utomo (Oto Rhino Laryngologica Indonesiana, 2023)
Background: Obstructive sleep apnea (OSA) is described as a disturbance of sleep presentingrepetitive (either total or partial) closure of the upper airway. Studies have demonstrated that OSA inthe middle-aged induces excessive daytime sleepiness; mood problems and poor quality of life. OSAis characterized by repetitive narrowing or obstruction of the upper airway during sleep, resultingin apnea or hypopnea. Patients with OSA have shown poor sleep quality. Purpose: To evaluate thepossible association between OSA and patients’ sleep quality. Literature review: OSA is a commonsleep disturbance classified by intermittent partial or total upper airway obstruction during sleep, causing intermittent hypoxemia, recurrent arousals, sleep fragmentation, and poor sleep quality. OSA is related to the quality of life, depression, and anxiety, but there were associations with acute stress which were reported by a few studies. Most of studies on OSA had collected data from moderate to severe sleep apnea in elderly patients and clinical settings. Continuous positive airway pressure (CPAP) therapy, which provides a mechanical pneumatic stent for the upper airway, is an effective treatment for OSA. As a rule, it is given via a nasal mask, and therefore patients should ideally keep their mouth closed during sleep. Conclusion: The literature review showed that there was a significant association between obstructive sleep apnea risk and sleep quality. The risk of increasing OSA among young people is associated with acute stress, and the relationship is mediated by sleep quality.Keywords: sleep apnea, continuous positive airway pressure, upper airway obstruction